The role of surface and structural similarities in the retrieval of realistic perceptual events. - Raynal, Lucas; Clément, Evelyne; Sander, Emmanuel (British Journal of Psychology, 2025)
This study investigated whether structural similarities (i.e. abstract frames, e.g. once bitten twice shy) can prevail over surface similarities (i.e. contexts, e.g. restaurant) in driving the retrieval of realistic events involving dynamic, multimodal and perceptually crowded data. After watching an initial set of video clips, participants had to indicate whether a new video clip, that shared surface similarities with an initial event and structural similarities with another one, elicited a retrieval. The results of Experiment 1A showed that retrieval was more likely to be elicited by structural rather than by surface similarities. Experiment 1B confirmed that the surface similarities manipulated in this study were strong enough to elicit substantial retrievals when the competing structural match was neutralized. The pattern of results obtained in Experiment 1A remained unchanged when the number of unrelated video clips within the initial set was increased. The findings suggest that structurally based retrievals still prevail when familiar structures underlie realistic perceptual events. They open new perspectives regarding the settings that promote structurally based retrievals in educational contexts where unfamiliar principles are introduced.